Reserch of features of cesium-137 fixation on clay minerals - Колябіна, Дар’я Олександрівна (Technology audit and production reserves, 2012)
The atticle describes the results of modeling the sorption of cesium-137 in three clay minerals (kaolinite, montmorillonite, palygorskite). Found that the exchange and non-exchange uptake of cesium-137 all of the clay minerals occurs on three types of active sites